Newborn Screening for Presymptomatic Diagnosis of Complement and Phagocyte Deficiencies - Dezfouli, Mahya; Bergström, Sofia; Skattum, Lillemor; Abolhassani, Hassan; Neiman, Maja; Torabi-Rahvar, Monireh; Franco Jarava, Clara; Martin-Nalda, Andrea; Ferrer Balaguer, Juana M.; Slade, Charlotte A.; Roos, Anja; Fernandez Pereira, Luis M.; et al. (Frontiers in Immunology, 2020)
The clinical outcomes of primary immunodeficiencies (PIDs) are greatly improved by accurate diagnosis early in life. However, it is not common to consider PIDs before the manifestation of severe clinical symptoms. Including PIDs in the nation-wide newborn screening programs will potentially improve survival and provide better disease management and preventive care in PID patients. This calls for the detection of disease biomarkers in blood and the use of dried blood spot samples, which is a part of routine newborn screening programs worldwide. Here, we developed a newborn screening method based on multiplex protein profiling for parallel diagnosis of 22 innate immunodeficiencies affecting the complement system and respiratory burst function in phagocytosis. The proposed method uses a small fraction of eluted blood from dried blood spots, and is applicable for population-scale performance. The diagnosis method is validated through a retrospective screening of immunodeficient patient samples. This diagnostic approach can pave the way for an earlier, more comprehensive and accurate diagnosis of complement and phagocytic disorders, which ultimately lead to a healthy and active life for the PID patients.